If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(34x + 23) = 17(28 + -1x) Reorder the terms: 7(23 + 34x) = 17(28 + -1x) (23 * 7 + 34x * 7) = 17(28 + -1x) (161 + 238x) = 17(28 + -1x) 161 + 238x = (28 * 17 + -1x * 17) 161 + 238x = (476 + -17x) Solving 161 + 238x = 476 + -17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17x' to each side of the equation. 161 + 238x + 17x = 476 + -17x + 17x Combine like terms: 238x + 17x = 255x 161 + 255x = 476 + -17x + 17x Combine like terms: -17x + 17x = 0 161 + 255x = 476 + 0 161 + 255x = 476 Add '-161' to each side of the equation. 161 + -161 + 255x = 476 + -161 Combine like terms: 161 + -161 = 0 0 + 255x = 476 + -161 255x = 476 + -161 Combine like terms: 476 + -161 = 315 255x = 315 Divide each side by '255'. x = 1.235294118 Simplifying x = 1.235294118
| 20a^2-49ab+30b^2=0 | | 14x=45x+3 | | 4-1/x=3/x2 | | 6(2n-3)=13n+18 | | 3.78= | | 2h+7=3h | | 4a+24=84 | | 5s=5s+4 | | 35x+2=9x+2 | | 45x+71=-12+45x | | 2x^3+4x^2+3x+1=0 | | 3x-5/2=x | | 4X-7=8X | | 5-7m=3m | | 5(x-10)=2(x+8) | | 14-3(2x-1-2(3x+1))=6x-1 | | 4x-20=3x+11 | | 4x^3-28x^2+48x-8=0 | | -2(-3b+4.8)=14.4 | | 6x^2-7xr+2r^2=0 | | y=8-2x-x^2 | | 5(x-10)=(x+8) | | 5b+4=3b-4 | | -26x+60=79+84x | | 3+5x=11+3x | | 5(x+10)2x=246 | | 3x*2xy+xy= | | A=6(2x-3)+2(3-2x) | | x^2=100+10x | | 6×1/2-7 | | 2x+35=5x-85 | | 10k=4k-16 |